REPRESENTASI KEHIDUPAN WARIA DI YOGYAKARTA (Melalui Foto Esai “Waria Setara Warga” Pada National Geographic Indonesia Edisi Januari 2017) - Ferrina, Allisa (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
This research talked about representation of waria life in Yogyakarta through essay photos by National Geographic Indonesia January 2017 edition. Object of this research is 5 essay photos in “Waria Setara Warga”, by Rachma Safitri as the photographer. The superiority of NGI as Magazine theres in the character of the photos. Photo of “Waria Setara Warga” representation about transgender living in Yogyakarta whom could live hand to hand and side by side with the society. NGI use photos as mediation of representation living in Yogyakarta. Issue about gender conclude by NGI as a global campaign from United State. So, in addition being a mediation for representation, NGI also make photography as a mediation for global campaign. Researcher wants to know how photography work as a mediation for representation the global campaign about gender issues. The result of this research is a photo of essay "Waria Setara Warga" is a transgender advocacy media.